Impacts on the self-esteem of mastectomized women: An integrative review (Research, Society and Development, 2021)
Women affected by breast cancer are constantly subjected to mastectomy, as the main form of treatment. At that moment, several feelings run from diagnosis to treatment, due to the importance of this organ to the female figure. To this end, we sought to analyze the aspects involved in the self-esteem of women with breast cancer and/or undergoing mastectomy. To achieve the objective, a study of integrative literature review of qualitative nature and descriptive character was carried out. After full reading of 60 studies indexed in the SciELO, BVS, LILACS, PubMed and Science Direct databases, obtained from the crossing between descriptors, 14 scientific articles were selected in English (50%), Portuguese (35, 7%) and Spanish (14.3%), with a predominance in 2019 (35.8%), followed by 2018 (28.6%) and 2017 (21.4%), while 2020 and 2021 presented the same quantitative (7.1%). In this context, among the most prevalent negative feelings in mastectomized women, feelings of inferiority, symptoms of depression, shame, isolation, pessimism, changes in body image and sexual satisfaction stand out. Therefore, the importance of the support network and breast reconstruction is emphasized, as it reflects positively on the reduction of symptoms triggered in the different situations in which women experience during their fight against breast cancer.